Dwudziestolecie międzywojenne w periodyzacji historycznojęzykowej — wizje i rewizje - Woźniak, Ewa (Acta Universitatis Lodziensis. Folia Linguistica, 2017)
The author tries to locate the interwar period in the context of language periodization. She presents two previous approaches: the one of Z. Klemensiewicz, S. Urbańczyk and S. Dubisz who included the years 1918–1939 into Modern Polish period and the other of A. Furdal, T. Smółkowa, and S. Borawski who considered the year 1918 as the beginning of the new epoch in the history of Polish language. The author’s proposition is to focus on the evaluation of Polish language in the years 1918–1939, instead of looking for a borderline between the Modern Polish period and contemporary one. The main reason for connecting the interwar period with the contemporary one and not with the Modern Polish period was the radical change in the use of language. The re-establishment of the Polish state triggered fast process of integration. It was the result of the state policy of language and development of mass communication.